Passive restoration of native woody vegetation and soil properties following Lantana camara clearing in the Kavango–Zambezi Transfrontier Conservation Area, Zimbabwe - Buhle Francis; Charlie M. Shackleton; James Gambiza (South African Journal of Botany, 2026)

Impacts of Lantana camara invasion on livelihoods: Household perceptions from the Kavango Zambezi Transfrontier Conservation Area, Zimbabwe - Buhle Francis; Charlie M. Shackleton (Biological Invasions, 2026)
Invasive alien plants (IAP) affect rural livelihoods in both positive and negative ways, yet few studies examine how these impacts are distributed across households and contribute to vulnerability. This study assessed Impacts of Lantana camara invasion on livelihoods: Household perceptions from the Kavango Zambezi Transfrontier Conservation Area, Zimbabwe. We conducted 300 household surveys and two focus group discussions with elders across four wards invaded by L. camara and evaluated household vulnerability using a vulnerability score. Elders reported that L. camara first invaded one ward in 1942 and spread to the others within 16 years, encroaching on grazing and arable lands, reducing livestock forage and crop productivity, and affecting livelihoods. While providing ecosystem services such as material for live fences, mosquito repellent, fruits, firewood, ornaments, and poultry protection, it also imposed losses associated with eradication efforts, loss of indigenous plants, forage shortages, and the harbouring of rodents and snakes. Households reported mean annual livelihood losses of approximately US$483 and gains of about US$716. These estimates are perception-based and should be interpreted as indicative of household-level livelihood trade-offs rather than precise economic values. Despite some households reporting substantial gains, these were unevenly distributed, with most households (62%) experiencing net negative outcomes. Most households (58%) were at moderate risk from invasion, while a few (2%) faced extreme risk. These findings highlight a complex socio-economic landscape in which some households gain while others lose, suggesting that management strategies should account for both gains and losses to avoid disadvantaging vulnerable groups.

A comparative borough-level analysis of the integration and stewardship of fruit trees in public spaces in London (UK) - Arlinda Hajzeri; Charlie M. Shackleton (Urban Forestry & Urban Greening, 2025)

Complex and interacting drivers of arable field abandonment in villages of the Eastern Cape and KwaZulu-Natal, South Africa - Sihle Pokwana; Charlie Shackleton (Land Use Policy, 2025)

Urban tree cover targets: The good, the bad and the SMART - Justin Morgenroth; Kieron Doick; Richard Hauer; Dexter H. Locke; Camilo Ordóñez Barona; Lara A. Roman; Tenley M. Conway; Cynnamon Dobbs; Peter Duinker; Natalie M. Gulsrud; C.Y. Jim; Andrew K. Koeser; et al. (Urban Forestry & Urban Greening, 2025)

Global trends in urban forest irrigation: Environmental influences, challenges and opportunities for sustainable practices across 109 cities worldwide - Manuel Esperon-Rodriguez; Rachael V Gallagher; Alessio Russo; Sally A Power; Pedro Calaza-Martínez; Tiago Capela Lourenço; Paloma Cariñanos; Ana Alice Eleuterio; Zhengfei Guo; Gervais Lee; Pierre Masselot; Robert I. Mcdonald; et al. (Sustainable Cities and Society, 2025)

Spatial synergies for urban foraging: A South African example - Mallika Sardeshpande; Charlie Shackleton (Ambio, 2025)
Urban foraging for wild plant and animal products is increasingly recognised for its multiple benefits for people and nature stewardship. Planning for foraging in urban greenspace is one way that foraging can be made more accessible, beneficial, and equitable. Here, we explore how foraging could be recognised and provided for in urban municipalities in eastern South Africa. We synthesise forager and land manager interviews, policy analysis, and iterative discussions to develop four land use configurations under which foraging could be planned for. Design principles for community-based natural resource management are used to assess the feasibility of each configuration. We identify stakeholders who would be involved in governing each configuration, and how urban foraging can co-produce desirable outcomes for their priorities. We list locally-specific actions to enable collaborative greenspace governance through urban foraging. We suggest some generally applicable design considerations and implications for each of the four configurations.

The distribution and abundance of woody invasive alien plants in small towns in Eastern Cape Province, South Africa - Tshepiso Collen Seboko; Sheunesu Ruwanza; Charlie Shackleton (Urban Ecosystems, 2024)
Invasive alien plants (IAPs) are rapidly increasing around the world, mainly due to land transformation, climate change, and urbanisation. Whilst urban areas are highly susceptible to invasion by IAPs, crucial information on the distribution and abundance of woody invaders in small towns is limited. Here, we determined the distribution and abundance of woody IAPs across different suburbs and land use types in 12 small towns in the Eastern Cape province of South Africa. We enumerated 38 427 individual woody IAPs, and their abundance and distribution varied across surveyed towns. Although species such as Melia azedarach , Pinus elliotti , Jacaranda mimosifolia , Eucalyptus camaldulensis , and Ligustrum lucidum were the most distributed, species density varied across towns. More than half of the woody IAPs were identified in affluent (56%) suburbs compared to the townships (23%), Central business district (CBD) (16%), and low-income housing neighbourhoods (5%). There were significant differences in woody IAPs distribution across different land use types, with more than half (54%) found in the residential areas compared to road verges (32%) and public urban green spaces (14%). Some socio-economic and environmental predictors such as town population, mean temperature, unemployment rate, and Gross domestic product (GDP) showed significant and positive correlations with woody IAPs species richness and density. Our findings suggest an uneven spatial distribution and diversity of woody IAPs across the different small towns, suburbs, and land use types in the region. It is recommended that small towns in South Africa need financial and human resources support to effectively manage IAPs.

Understanding foraging practices in Lagos metropolis to redesign urban greenspaces in support of human-nature interactions - Opeyemi Adeyemi; Charlie M. Shackleton (Urban Forestry & Urban Greening, 2023)

Unsustainable trade-offs: provisioning ecosystem services in rapidly changing Likangala River catchment in southern Malawi - Deepa Pullanikkatil; Penelope J. Mograbi; Lobina Palamuleni; Tabukeli Ruhiiga; Charlie Shackleton (Environment, Development and Sustainability, 2020)

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

A spatio-temporal, landscape perspective on Acacia dealbata invasions and broader land use and cover changes in the northern Eastern Cape, South Africa - Aidan John Gouws; Charlie M. Shackleton (Environmental Monitoring and Assessment, 2019)

Community-based natural resource use and management of Bigodi Wetland Sanctuary, Uganda, for livelihood benefits - A. Gosling; Charlie M. Shackleton; J. Gambiza (Wetlands Ecology and Management, 2017)

Woody plant species richness, composition and structure in urban sacred sites, Grahamstown, South Africa - P. De Lacy; Charlie M. Shackleton (Urban Ecosystems, 2017)

Impacts of HIV / AIDS on food consumption and wild food use in rural South Africa - Keitometsi Ncube; Charlie M. Shackleton; Brent M. Swallow; Wijaya Dassanayake (Food Security, 2016)

Knowledge, perceptions and willingness to control designated invasive tree species in urban household gardens in South Africa - Charlie M. Shackleton; R. T. Shackleton (Biological Invasions, 2016)

Ecological Knowledge Among Communities, Managers and Scientists: Bridging Divergent Perspectives to Improve Forest Management Outcomes - Lucy Rist; Charlie Shackleton; Lily Gadamus; F. Stuart Chapin; C. Made Gowda; Siddappa Setty; Ramesh Kannan; R. Uma Shaanker (Environmental Management, 2016)

The benefits from and barriers to participation in civic environmental organisations in South Africa - Olivia Higgins; Charlie M. Shackleton (Biodiversity and Conservation, 2015)

Homestead greening is widespread amongst the urban poor in three medium-sized South African towns - Humphrey Kaoma; Charlie M. Shackleton (Urban Ecosystems, 2014)

Contrasting architecture of key A frican and A ustralian savanna tree taxa drives intercontinental structural divergence - Glenn R. Moncrieff; Caroline E. R. Lehmann; Jan Schnitzler; James Gambiza; Pierre Hiernaux; Casey M. Ryan; Charlie M. Shackleton; Richard J. Williams; Steven I. Higgins (Global Ecology and Biogeography, 2014)
Aim We examined differences in the architecture of A frican and A ustralian savanna trees. We sought to attribute variation in tree architecture to current environments, wood density and phylogeny, and thereby elucidate the relative importance of biogeographic idiosyncrasies versus current factors in underpinning architectural differences. Location A frica and A ustralia. Methods We compiled canopy diameters and stem diameters from 4867 trees of 97 species and heights and stem diameters from 10,786 trees of 155 species from a range of A frican and A ustralian savanna ecosystems and climates. Using B ayesian methods we first estimated continental‐scale savanna tree allometries, ignoring species differences. We then examined continental differences in species‐specific allometries accounting for trait covariation using a phylogeny of our study species. Environmental variables and wood density data were included as covariates, allowing us to assess the potential underpinning of regional differences in tree allometries by differences in current environments and traits. Results Substantial allometric differences exist between A ustralian and A frican savanna trees. A ustralian trees are on average 6 m taller at 20 cm diameter, with a 53% smaller canopy area than A frican trees. However, this extreme continental‐scale variation is driven by the architecture of only a few taxa in this study – V achellia and S enegalia versus E ucalyptus and C orymbia – rather than systematic differences between species, wood density and environment. These same genera often dominate the woody strata of S outh A frican and A ustralian savannas, respectively. Main conclusions Stark differences in the architecture of A frican and A ustralian savanna tree taxa are not a product of environmental differences and are not consistent across species. Rather, the most likely explanation is the different evolutionary histories of A frican and A ustralian savannas, which share no woody species. We consider that these architectural differences are likely to impact regional patterns of woody biomass accumulation.

Invasive alien species as drivers in socio-ecological systems: local adaptations towards use of Lantana in Southern India - Ramesh Kannan; Charlie M. Shackleton; R. Uma Shaanker (Environment, Development and Sustainability, 2014)

Reconstructing the history of introduction and spread of the invasive species, Lantana, at three spatial scales in India - Ramesh Kannan; Charlie M. Shackleton; R. Uma Shaanker (Biological Invasions, 2013)

Conservation, commercialisation and confusion: harvesting of Ischyrolepis in a coastal forest, South Africa - Charlie M. Shackleton; Fiona Parkin; Maphambe I. Chauke; Linda Downsborough; Ashleigh Olsen; Gregg Brill; Craig Weideman (Environment, Development and Sustainability, 2009)

Household attributes promote diversity of tree holdings in rural areas, South Africa - Charlie M. Shackleton; Fiona Paumgarten; Michelle L. Cocks (Agroforestry Systems, 2008)

Growth and fruit production of Sclerocarya birrea in the South African lowveld - Charlie Shackleton (Agroforestry Systems, 2002)

Nearest-neighbour analysis and the prevelance of woody plant competition in South African savannas - Charlie Shackleton (Plant Ecology, 2002)

Changes in woody community structure and composition under constrasting landuse systems in a semi‐arid savanna, South Africa - Steven I. Higgins; Charlie M. Shackleton; E. Robbie Robinson (Journal of Biogeography, 1999)
Summary We aimed to explore the farm scale effects of three landuse types, communal grazing, wildlife management and commercial cattle farming, on the woody vegetation of a semiarid savanna. Location The study farms were located within a single bioclimatic zone in semiarid savanna, South Africa. Methods The species composition and structure of woody vegetation on three farms of each of three landuse types were sampled. Results We found that communal grazing land sites were classified outside the topland‐bottomland vegetation dichotomy characteristic of this region. Comparisons of size class distributions showed the communal grazing lands had fewer small and large individuals; suggesting both lower levels of regeneration and regenerative capacity in the communal grazing lands. The species richness and biomass of woody plants was lower on communal grazing lands than on private game reserves and commercial cattle farms. The longevity of tree species explains the observed lag between changes in abundance and species loss; we consequently predict that there will be future losses of species in the communal grazing lands. By classifying species into a range of use‐categories we showed that utilization and species loss was not limited to certain plant use categories. Higher levels of wood harvesting measured in the communal grazing lands are likely to be responsible for the observed differences. Main conclusions It is concluded that communal grazing management at this study site has substantially changed the composition and structure of woody plant communities, and that these changes have reduced the current availability of natural resources and will reduce resource production in the future.

Rainfall and topo‐edaphic influences on woody community phenology in South African savannas - Charlie M Shackleton (Global Ecology and Biogeography, 1999)
Woody community phenology was studied in the central lowveld, South Africa, over a twelve month period at three sites along a rainfall gradient, with both toplands and bottomlands sampled at each site. Each month, individual plants, in replicated samples, were scored into a number of categories describing their phenological state. Position on the rainfall gradient influenced: (1) onset and magnitude of leaf emergence, (2) onset and duration of mature leaves, and (3) the proportion of leafless trees. Generally, the moist site demonstrated earlier leaf growth than the intermediate or arid sites. Emergent and mature leaves were recorded earlier, and in the case of mature leaves, retained longer. Overall, there was a lower proportion of leafless trees during the dry season at the moist site, followed by the semi‐arid site, followed by the arid site. Differences with respect to catenal position were evident for the proportion of trees in winter with mature leaves, and the proportion of trees with senescent leaves. Bottomlands had a greater proportion of trees with leaves during winter, but a lower proportion of trees recorded with senescent leaves. Both of these findings were a result of the greater proportion of evergreen species in bottomlands, as well as increased leaf retention by the deciduous species. Phenological activity of leaves was related to plant stem size. In particular, there was greater leaf retention during the dry period by small stems, relative to large stems.